Intracranial hemorrhage during aeromedical transport and correlation with high altitude adaptations in the brain - Kouliev T; Richardson A; Glushak C (Open Access Emergency Medicine, 2012)
Timur Kouliev,1 Airron Richardson,2 Cai Glushak3,41Beijing United Family Hospital, Beijing, People's Republic of China; 2Department of Emergency Medicine, The Methodist Hospitals, Gary, IN, 3AXA Assistance USA, Chicago, IL; 4Section of Emergency Medicine, University of Chicago, Chicago, IL, USAAbstract: Aeromedical transport is challenging not only because of limitations of equipment, unfamiliar surroundings, and challenging environmental conditions, but also due to difficulty in developing methodologies for research and data collection. To our knowledge, neurological changes at the oxygen tensions of a pressurized cabin have not been systematically studied. Here we report a case of intracranial hemorrhage during aeromedical transport and review the body's cardiovascular and respiratory adaptation to decreased ambient oxygen tension. Previous experience with high altitude cerebral edema serves as guidance for mitigating the effects of vasogenic edema in patients at risk of neurological events who travel by air. Review of this case and relevant altitude-related physiological changes may be grounds for more conservative recommendations on aeromedical transport after an acute neurological event.Keywords: pediatric, disaster, triage, equity, pregnancy, survival